Kualitas fisik daging Itik Peking dengan penambahan Azzola pinnata dalam ransum - Emy, Emy Saelan; Yunus Syafie; Sulasmi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Research on the physical quality of Peking duck meat with the addition of Azzola pinnata in the ration was carried out at the Animal Husbandry Laboratory, Faculty of Agriculture, Khairun University and rearing of ducks was carried out at the Sasa Mandiri Book Cage, Sasa Puncak Village, South Ternate District. Research used 80 Peking ducks aged 1 weeks, consisting of 4 treatments and 5 replications namely: P0 100% basal ration; P1 basal ration 90% + Azzola pinnata 10%; P2 basal ration 80% + Azzola pinnata 20%; and P3 basal ration 70% + Azzola pinnata 30%. The physical quality of meat, 20 ducks were used.  The variables observed include pH, water content, cooking loss and water holding capacity. Research was analyzed using a Completely Rendomized Design (CRD) and if there were differences, it was continued with Duncen’s Multiple Distance Test. The results of research on the physical quality of Peking duck meat showed that the pH value and cooking loss were not significantly different (P>0,05), but the percentage of water content and water holding capacity showed significant differences (P<0,05). The average pH ranges from 5,80 – 5,88%, water content 71,49 – 73,21%, cooking loss 35,40 – 36,64% and water holding capacity 50.53 – 58.51%. The conclusion from this research is that giving Azzola pinnata in the ration up to 20% can improved the physical quality of duck meat.